THE COLLOCATION MEANING OF “VACCINE” ON SEMANTIC APPROACH: A CORPUS-BASED ANALYSIS - Wulansari Wulansari (Haluan Sastra Budaya, 2021)
Corpus semantics examines the words that are used in text and discourse using observations as evidence of meaning. This study aims to investigate the collocations of node ‘vaccine’ based on semantic preference and semantic prosody using the corpus-based approach since the source of data is the corpus data. The qualitative research method is used to find the hypotheses from the corpus data taken from sub-corpus in Covid-19 corpus using Sketch Engine software. This study demonstrates that the node word of ‘vaccine’ in the semantic preference was shown six words related to the Covid-19 corpus. Meanwhile, the category of semantic prosody was displayed four words negative in meaning, and there was two words displayed positive in meaning, the collocations with negative meaning which occur more frequently than positive meaning. Thus, the writer concluded that the author of a reputable journal explained the word ‘vaccine’ with a negative perspective in Covid-19.